2012
DOI: 10.1111/j.1099-0860.2011.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Palestinian Children: Authors of Collective Memory

Abstract: This article investigates the premise that Palestinian children are the authors of collective memory. Palestinian society employs an oral tradition that propagates the collective experience among different generations in which the individual dimensions of each is apparent. The oral history for Palestinian children not only illustrates past events, it also provides the tool for grasping the present and traversing the future. In this ethnographic study, 12 Palestinian children from cities, villages and refugee c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
1
20
0
2
Order By: Relevance
“…Connecting work on memory and geopolitics need not be restricted to post‐conflict settings like the Falkland Islands, as children and young people have sensorial, embodied and intergenerational encounters with memory in many diverse contexts as previous research has observed (e.g. Berliner ; Habashi ; Kuusisto‐Arponen ; Tolia‐Kelly ). These ideas help to shift the focus beyond the spaces, representations and practices that have typically received attention in studies exploring the formation of young people's national and (geo)political identities, such as the school classroom, textbooks and official commemorative performances.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Connecting work on memory and geopolitics need not be restricted to post‐conflict settings like the Falkland Islands, as children and young people have sensorial, embodied and intergenerational encounters with memory in many diverse contexts as previous research has observed (e.g. Berliner ; Habashi ; Kuusisto‐Arponen ; Tolia‐Kelly ). These ideas help to shift the focus beyond the spaces, representations and practices that have typically received attention in studies exploring the formation of young people's national and (geo)political identities, such as the school classroom, textbooks and official commemorative performances.…”
Section: Resultsmentioning
confidence: 99%
“…The Memorial Wood works to perpetuate a specific mode of remembrance intended to ‘embody continuity’, a continuity that was to be sustained in symbolically important ways by the next generation of Islanders (Assmann , 282). They were seen here as the cultivator and ‘keeper of collective memories that previous generations experienced’ in ways that, it was suggested, offered catharsis for veterans and families of the fallen (Habashi , 421). The embodied performances of young people ‘planting’ and ‘looking after’ the wood were laden with symbolism that rooted and reproduced memory in place.…”
Section: Putting Memory To Work In Placementioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it shows how young Falkland Islanders can respond, contest and shape debates concerning the geopolitical relations that characterise their lives (and those of their forebears), through online engagements with social media, for instance. Youth, then, can be considered as agents of (in)security with the capacity to formulate ideas about security, influenced by memories of past geopolitical events, but also contextualised within the dynamics of contemporary international relations (Benwell, 2016b;Berliner, 2005;Becker, 2014;Habashi, 2013).…”
Section: (P 209)mentioning
confidence: 99%
“…Collective memory is heavily bound up with national and group identity. Habashi (2013) offers one strong example in the oral story-telling practices of Palestinian children. She shows how such practices serve to underline feelings of community, unity and continuity.…”
Section: Collective Memory Civil Society and Democracymentioning
confidence: 99%